Insuficiencia de convergencia en paciente femenino de 50 años. - Celi Henríquez, Flavio Steven (2022)
The present clinical case analyzes a 50-year-old female patient with a diagnosis of convergence insufficiency or also called CI, which consists of a visual problem where the eyes, when working together, present some difficulty when looking at close objects. The objective of this study is to determine the causes of convergence insufficiency in a 50-year-old female patient, and for its execution the methodology based on the analysis of the clinical history, physical examinations (AR- Autorrefractometer, AVL, AVC, AVCC, PPC, ocular motility, cover test, fundus and biomicroscopy) was used, fundus and biomicroscopy) and complementary examinations that allowed making a presumptive, differential and definitive diagnosis, as well as prescribing a treatment according to the symptoms presented by the patient, which correspond to headache, blurred vision, difficulty in concentration and asthenopia, which affect her daily activities. The treatment prescribed to mitigate the visual problem presented by the patient is a visual therapy called "Push-Up" and the use of glasses every time she performs near tasks, which will allow her to reduce her convergence insufficiency problem.